Curse of the ancients - De la Pena, Matt. (New York, NY : Scholastic Inc., 2013)
Sera has seen the future, and it is terrifying. Unfortunately, she can't do anything to prevent the Cataclysm while stranded with Dak and Riq thousands of years in the past. Their only hope lies with the ancient Maya, a mysterious people who claim to know a great deal about the future. Is there more to these ancients than meets the eye?
105651
Keywords: Mayas -- Civilization -- Juvenile fiction; Time travel -- Juvenile fiction; Conspiracies -- Juvenile fiction; Best friends -- Juvenile fiction; World history -- Fiction; Fantasy; Adventure fiction; Science fiction; Friendship -- Fiction; Adventure stories; Children's stories; Time Travel; Fantasy fiction; Science fiction